Guerra Civil, Madrid / Fernando Martínez de Baǫs Carrillo, coordinador ; José Juan Arilla Herrero ... [et al.] - Martínez de Baǫs Carrillo, FernandoArilla Herrero, José Juan (Historia; 9)
Índice onomástico